ASSURE MODEL FOR TEACHING SPEAKING ONLINE: TEACHER SELF REFLECTIONS - Prihatmi, Tutut Nani; Istiqoma, Maria; Anjarwati, Rini (Jurnal Ilmiah Langue and Parole, 2021)
Transferring the form of face-to-face learning in conventional classes to online learning is not only as simple as changing learning materials into all-digitalization as not all teachers try to make a proper and organized preparation before starting the online teaching process. With the limited time to practice speaking skills at the National Institute of Technology Malang, the teachers are expected to have the right planning and strategies for their classes. Therefore, this paper reports on the the use of ASSURE model in teaching speaking online from the perspective of two English teachers in the National Institute of Technology Malang. This qualitative study relied primarily on in-depth interviews of the two teachers to gather the information. This research’s findings and recommendations are expected to help provide insights in preparing and developing other online speaking classes to achieve better outcomes.